Autonomous fault diagnosis of commercially available PV modules using high-end deep learning frameworks - Tasawar, Ihtyaz Kader; Tanzeem, Abyaz Kader; Ahmed, Tahmid; Zarin, Shah Faiza (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.